The Eurosystem Household Finance and Consumption Survey - Methodological report (European Central Bank (ECB), 2013)
This report summarises the methodologies used in the first wave of the Eurosystem Household Finance and Consumption Survey, which provides household-level data collected in a harmonised way in 15 euro area countries for a sample of more than 62,000 households. The report presents the methodologies applied in areas such as data collection, sample design, weighting, imputation, and variance estimation. It also analyses issues like differential unit and item non-response and other issues that may have an effect on the comparability of the survey data across countries
Keywords: D12; D14; D31; 330; household-level data; multiple imputation; statistical disclosure control; survey methodology; variance estimation; wealth